2008
DOI: 10.1007/s10509-008-9841-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of perturbations, radiation and oblateness on the periodic orbits in the restricted three-body problem

Abstract: This paper investigates the periodic orbits around the triangular equilibrium points for 0 < μ < μ c , where μ c is the critical mass value, under the combined influence of small perturbations in the Coriolis and the centrifugal forces respectively, together with the effects of oblateness and radiation pressures of the primaries. It is found that the perturbing forces affect the period, orientation and the eccentricities of the long and short periodic orbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 5 publications
3
30
0
Order By: Relevance
“…We choose the unit of time such as to make the gravitation constant equal to unity. Let the coordinates of the infinitesimal mass be (x, y) and those of masses m 1 , m 2 and m 3 are: is the oblateness coefficient of m 2 with R e and R p , as the equatorial and polar radii, respectively, and R is the separation between the primaries. In general, we have 0 < A 2 << 1.…”
Section: Equations Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…We choose the unit of time such as to make the gravitation constant equal to unity. Let the coordinates of the infinitesimal mass be (x, y) and those of masses m 1 , m 2 and m 3 are: is the oblateness coefficient of m 2 with R e and R p , as the equatorial and polar radii, respectively, and R is the separation between the primaries. In general, we have 0 < A 2 << 1.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…In recent time, many researchers have taken into account the effects of radiation and oblateness in their study of restricted threebody problem [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…and λ 1,2,3,4 are given by (24). If at time t = 0, initial conditions are X = X 0 , Y = Y 0 ,Ẋ =Ẋ 0 anḋ Y =Ẏ 0 then four arbitrary constant P j and hence, constants Q j are determined from the solution of the four simultaneous linear equations…”
Section: Stability Analysismentioning
confidence: 99%
“…which are sufficiently oblate. In literature, a number of researchers as [20], [21], [22], [23], [24], [25], [13], [26], [14] etc. have studied different aspects of restricted three body problem (RTBP), by taking one or both primary as source of radiation or oblate spheroid or both and have discussed their effects on the motion of infinitesimal mass.…”
Section: Introductionmentioning
confidence: 99%
“…They have discussed also the spectral stability and their bifurcations with all the possible configurations. AbdulRaheem et al in [1,2] studied the stability and periodic orbits of equilibrium points in the restricted three-body problem under the effect of radiation, oblateness, and perturbing forces. They observed that the perturbing forces affect the stability, period, orientation, and the eccentricities of the long and short periodic orbits.…”
Section: Introductionmentioning
confidence: 99%